2003
DOI: 10.1105/tpc.011965
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Expansin Gene Expression Affects Growth and Development in Transgenic Rice Plants

Abstract: To investigate the in vivo functions of expansins, we generated transgenic rice plants that express sense and antisense constructs of the expansin gene OsEXP4 . In adult plants with constitutive OsEXP4 expression, 12% of overexpressors were taller and 88% were shorter than the average control plants, and most overexpressors developed at least two additional leaves. Antisense plants were shorter and flowered earlier than the average control plants. In transgenic plants with inducible OsEXP4 expression, we obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
213
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(225 citation statements)
references
References 50 publications
11
213
0
1
Order By: Relevance
“…This hypothesis is supported by the expression analysis of cell cycle marker genes that revealed a more rapid down-regulation of mitotic genes and an up-regulation of the cell cycle inhibitory genes in the samba mutants. The EXP11 gene expression was also upregulated, in agreement with data showing that the ectopic expression of EXPANSIN genes stimulate plant growth and suppression by gene silencing reduces it (42,43). Furthermore, microarray analysis showed that in samba knockout plants, the ethylene signal transduction was clearly overrepresented, which plays a prominent role in cell division regulation during leaf development by arresting the cell cycle (44).…”
Section: Discussionsupporting
confidence: 73%
“…This hypothesis is supported by the expression analysis of cell cycle marker genes that revealed a more rapid down-regulation of mitotic genes and an up-regulation of the cell cycle inhibitory genes in the samba mutants. The EXP11 gene expression was also upregulated, in agreement with data showing that the ectopic expression of EXPANSIN genes stimulate plant growth and suppression by gene silencing reduces it (42,43). Furthermore, microarray analysis showed that in samba knockout plants, the ethylene signal transduction was clearly overrepresented, which plays a prominent role in cell division regulation during leaf development by arresting the cell cycle (44).…”
Section: Discussionsupporting
confidence: 73%
“…Expression levels of b-EXPANSIN4, another cell wallloosening enzyme, were negatively correlated with leaf size traits (Fig. 7), although up-and down-regulation of expansin expression in Arabidopsis and rice resulted in larger and smaller leaves, respectively (Cho and Cosgrove, 2000;Choi et al, 2003;Goh et al, 2012). However, more pleiotropic phenotypes were observed after constitutive modification of expansin gene expression, including a reduction in overall plant growth (Rochange and McQueen-Mason, 2000), demonstrating that the effect of expansin expression on leaf growth is context dependent and influenced by the growth phase of the leaf (Sloan et al, 2009).…”
Section: Leaf Growth Is Strongly Correlated With Cell Wall Characterimentioning
confidence: 99%
“…Exogenous ABA application restricts elongation because of reduced tissue responsiveness to GA. Farther downstream, induction of the expression and activity of expansins facilitates cellular expansion and growth (Choi et al, 2003). Shoot elongation is a quantitative trait attributed primarily to the SNORKEL (SK) locus on chromosome 12, which together with two other loci on chromosomes 1 and 3, can account for the full escape response (Hattori et al, 2008(Hattori et al, , 2009(Hattori et al, , 2011.…”
Section: Escapementioning
confidence: 99%